Carbohydrate availability in female endurance athletes with symptoms of Relative Energy Deficiency in Sport (RED-S) - Graefnings, M.; Lysdal Fahrenholtz, I.; Klungland Torstveit, M.; Garthe, I.; Melin, A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Endurance athletes with high training loads and weight focus have increased risk of low energy and carbohydrate (CHO) availability. Sufficient CHO availability throughout the day is needed to provide substrate to e.g., muscles and hypothalamic-pituitary hormone production. The aim of this study was to investigate the dietary intake with special focus on timing of CHO intake in relation to training load in athletes with symptoms of Relative Energy Deficiency in Sport (RED-S).